Avaliação comparada da ação antioxidante de N-acetil-l-cisteína (nac) e o extrato de caule da Coutarea hexandra (rubiaceae) sobre os efeitos sistêmicos do envenenamento experimental por Lachesis muta muta (surucucu sul-americana) em ratos - TORRES, Aline Graciele Leão (2022)
The present study investigated the potential use of N-acetyl-L-cysteine (NAC) in association with a polyvalent antivenom and as a stand-alone therapy to reduce the acute local and systemic effects induced by Lachesis muta muta venom in rats. Male Wistar rats (300–350 g) were exposed to L. m. muta venom (1.5 mg/kg – i.m.) and subsequently treated with anti-Bothrops/Lachesis serum (antivenom:venom ratio 1:3 'v/w' – i.p.) and NAC (150 mg/kg – i.p.) separately or in association; animals were monitored for 120 min to assess changes in temperature, locomotor activity, local edema formation and the prevalence of hemorrhage. Then, the animals were anesthetized and euthanized to collect tissue samples; hematological-biochemical and histopathological analyzes were performed via conventional methods. The poison of L. m. muta produced marked local edema, subcutaneous hemorrhage and myonecrosis, with both antivenom and NAC successfully reducing the extent of myonecrotic damage when individually administered; their association also prevented the occurrence of subcutaneous hemorrhage. Venom-induced serum creatine kinase (CK) release was significantly prevented by NAC alone or in combination with antivenom; The venom induced a significant increase in leukocytes which was also associated with an increase in neutrophils, eosinophils and monocytes; antivenom and NAC partially reduced these changes, with NAC alone significantly preventing the increase in eosinophils whereas neither NAC or antivenom prevented the increase in monocytes. The antioxidant drug N-acetyl-L-cysteine (NAC) shows potential as a supportive therapeutic agent to attenuate the acute local effects of Lachesis m envenomation. mutate. This study is the first to show the value of NAC in treating Lachesis envenomation. Together, these findings may further support the idea of using a pharmacological intervention against envenoming that would attenuate its effects in the absence of antivenom therapy.